2011
DOI: 10.1089/pop.2010.0057
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Osteoporosis Screening Completion Rates in a Primary Care Practice

Abstract: The United States Preventive Services Task Force and the National Osteoporosis Foundation recommend routine osteoporosis screening for women aged 65 years or older. Previous studies have shown that the use of a clinical decision-support tool significantly improves screening rates. In a recently published study, a statistically significant improvement was found in the screening rates for eligible women with use of the tool. To evaluate whether a clinical decision-support tool independently predicts completion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
5
0
6
Order By: Relevance
“…Professor Hsu rightfully mentioned the impact that certain factors can have on osteoporosis screening. After this paper's publication, we had subsequently reported on predictors of osteoporosis screening completion in our practice using the same population group and covering similar time frames [1]. We found that factors associated with increased likelihood of screening completion included race, marital status, presence of certain co-morbidity (cancer, rheumatologic diseases) and type of clinic visit (general exam visit).…”
Section: To the Editormentioning
confidence: 93%
“…Professor Hsu rightfully mentioned the impact that certain factors can have on osteoporosis screening. After this paper's publication, we had subsequently reported on predictors of osteoporosis screening completion in our practice using the same population group and covering similar time frames [1]. We found that factors associated with increased likelihood of screening completion included race, marital status, presence of certain co-morbidity (cancer, rheumatologic diseases) and type of clinic visit (general exam visit).…”
Section: To the Editormentioning
confidence: 93%
“…A 1997 study showed that patients with chronic illness were less likely to receive recommended preventive services, 3 as did a more recent report focused only on patients with diabetes mellitus. 4 In contrast, other reports have shown positive associations between chronic disease comorbidity and osteoporosis screening, 5 and between rheumatoid arthritis and dyslipidemia and osteoporosis screening. 6 …”
mentioning
confidence: 93%
“…Increasing rates of BMD screening fills a clinical need as previous studies have demonstrated adherence rates to screening guidelines of 12 to 56% across groups and 19 to 97% among individual physicians [15, 16]. While one might presume providers and patients adhering to screening recommendations for colon cancer and polyps would also adhere to osteoporosis screening guidelines, 32.1% of the patients for whom BMD screening was indicated in this study had not undergone screening.…”
Section: Discussionmentioning
confidence: 76%